Implementation of the Slum-Free City Policy to Increase Infrastructure Development in Tangerang City - Muhtadi, Tb. Yudi; Damayanti, Damayanti; Riyaj, Mohd (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
This research aims to determine the implementation of the Slum-Free City Policy in increasing infrastructure development in Tangerang District, Tangerang City. This research method uses a qualitative method with a descriptive approach, while this type of research uses a case study. The research carried out was descriptive qualitative research. Conclusion: Implementation of the Slum-Free City Policy program is an interest that can influence the implementation of the program. Supervision carried out by the BKM chairman for each sub-district implementation in the City without Slums program is in the interests of BKM. In carrying out an evaluation of the level of usefulness for the community regarding the City Without Slums program in Tangerang District. Most of it can be explained by the presence of the City Without Slums Program, which has not been implemented comprehensively